COMMUNICATION ON EMPOWERMENT OF JOINT BUSINESS GROUPS (KUBE) BY THE PROBOLINGGO REGENCY SOCIAL SERVICE: (Case Study on KUBE Keluarga Harapan in Asembagus Village, Kraksaan District, Probolinggo Regency) - Candra, Efdon Dwy; Dharmawan, Awang (The Commercium, 2024)
Poverty is one of the problems in Probolinggo Regency, the Probolinggo Regency Social Service has made various efforts to reduce the level of poverty. One of them is through a Joint Business Group (KUBE)-based empowerment program such as that carried out for the Harapan Family KUBE in Asembagus Village, Kraksaan District, Probolinggo Regency. The success of this program in reducing the level of poverty is closely related to the empowerment communication carried out by the Probolinggo Regency Social Service. In this regard, the aim of this research is to determine the empowerment communication applied in the KUBE Keluarga Harapan empowerment program so that it can be as successful as it is now using Miles and Huberman's analysis and Wilbur Schramm's communication theory.. This research is qualitative research with a case study method. Data was obtained from interviews, observation and documentation. The results of this research show that the KUBE-based empowerment program carried out by the Probolinggo Regency Social Service uses the concept of participatory empowerment communication. Coordination carried out with various parties gave rise to consensus and synergy in making the program a success. Group mentors also build good relationships with the group they accompany so that it has an impact on the survival and sustainability of the group.